1990
DOI: 10.3164/jcbn.8.193
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-mimetic action of vanadyl complexes.

Abstract: SummaryBlood glucose levels of streptozocin (STZ)-induced diabetic rats dropped from hyperglycemic levels to hypoglycemic levels within 24-48 h after treatment with vanadyl sulfate (VS) by intraperitoneal injection. Results of the glucose tolerance test indicated that the diabetes was completely improved by VS administration, but the plasma insulin levels were still low. Determination of both vanadyl and total vanadium in VS-treated STZ-rats suggested that the vanadyl is possibly in a pharmacologically active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 30 publications
5
56
0
Order By: Relevance
“…[ [21][22], and its complexes [23][24][25][26] by oral administration has been demonstrated in the streptozotocin-induced diabetic rats (STZ-rats). The mechanism for the action of vanadium has been proposed from the results showing stimulation of glycogen synthesis, glucose uptake into the adipocytes [27,28] and free fatty acid (FFA) release from adipocytes [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ [21][22], and its complexes [23][24][25][26] by oral administration has been demonstrated in the streptozotocin-induced diabetic rats (STZ-rats). The mechanism for the action of vanadium has been proposed from the results showing stimulation of glycogen synthesis, glucose uptake into the adipocytes [27,28] and free fatty acid (FFA) release from adipocytes [27].…”
Section: Discussionmentioning
confidence: 99%
“…We are studying the development of orally active vanadium complex to treat IDDM. Recently, we have proposed that bis(picolinato)oxovanadium (VO-PA) complex is effective by oral administration to treat the diabetes of STZ-rats [26] after the fundamental investigations on vanadyl complexes with various coordination modes such as VO(04) [23], VO(S2N2) [23] and VO(S4) [25]. The results indicated that the VO-PA complex with VO(N202) coordination mode was useful for developing new vanadyl complexes as a leading compound with hypoglycemic activity.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,27) In 1995, we proposed a new in vitro assay, based on the inhibition of FFA (free fatty acids)-release from isolated rat adipocytes treated with epinephrine (adrenalin), which is simple and convenient compared with the use of RI reagents. 35) By this in vitro assay, we have evaluated some insulin-mimetic activities of vanadyl complexes with different chemical structures and coordination modes such as VO(O 4 ), 36) VO(N 2 O 2 ), [37][38][39][40][41][42][43] VO(S 2 N 2 ), 36) VO(S 2 O 2 ), 44,45) VO(N 3 O), 39) and VO(N 4 ). 28) Our results indicate that the complexes with a strong ability to inhibit FFA-release from adipocytes lowered the high blood glucose levels in type 1 and 2 diabetic animals more effectively than VOSO 4 .…”
mentioning
confidence: 99%
“…[5][6][7] In recent years, several reports have documented vanadium therapyinduced improvements in insulin sensitivity in the liver and muscles of many type 2 diabetic human subjects. [8][9][10] Since the discovery of the orally active insulin-mimetic oxovanadium(IV)-cysteine methyl ester complex for the treatment of streptozotocin (STZ)-induced diabetic rats in 1990, 11 the therapeutic potential of oxovanadium(IV) complexes has been of great interest to us. We and other researchers have developed several types of oxovanadium(IV) complexes with different vanadium coordination spheres, such as VO(N 2 S 2 ), VO(N 2 O 2 ), VO(S 2 O 2 ), VO(O 4 ), and VO(S 4 ).…”
mentioning
confidence: 99%